(untitled) (Journal of Education and Development, 2019)
This article analyses the Italian school system vis-à-vis other European systems from an objective perspective; the paper seeks to do this by elucidating some of its opaque aspects. It engages with an idea of cultural identity and what can be identified as the most obvious threats posed to it; Italy’s Gestalt at present is coterminous with that of the extant European educational framework, which formerly Italians themselves worked hard to bring about. Hence, raising awareness as to the modality that our country’s laws and agreements impact all aspects of our society becomes a main educational concern in this field of study.